Boron toxicity in Lemna gibba - Sánchez Villavicencio, Mayra; Álvarez Silva, Carlos; Miranda Arce, Guadalupe (HIDROBIOLÓGICA, 2017)
Total soluble phenols and total chlorophylls content, changes of biomass and concentration factor in Lemna gibba exposed to different concentrations of boron were measured. Day six soluble phenols showed significant differences in treatment with 10 mg/L of boron. At day ten, chlorophylls content in treatment 2 mg/L concentration increased respect to other experimental groups and control group, there were no significant differences. Biomass of Lemna gibba decreased significant in treatments with 1.5 and 2.5 mg/L treatments of boron. The highest Bioconcentration factor was found in 0.25 mg/L of boron, this accumulation is not relevant. Lemna gibba showed tolerance in the presence of boron in concentrations used here. Suggesting that this aquatic macrophyte could be used for tertiary treatment and the possible renewal wastewater contaminated with boron.